Parábola do Cágado Velho: entre ficção e história, (dis) utopias - Góes, Eliane Rosa de (2011)
Study of the novelistic structure of Parábola do Cágado Velho (2005), by Angolan writer Pepetela or Artur Carlos Maurício Pestana dos Santos, who reenacts in his fiction the history of Angola in the universal context. Among the ethnic and linguistic, socio-economic, political and religious disparities raised, the denial of hopeful utopian projections gave place to dystopias reversals. On the basis of the reversal of the utopian gender, the dystopia acts as a non-place and a way of thinking new models in Pepetela s novel, as they are incorporated into the utopian essence of Parábola do Cágado Velho. From the mythical tradition emerges a reading of the narrative plot in the form of a review and dialogue on the relationship between past and present, suggesting historical changes for the future and other so-called meta-utopias. In these, the idea of continuity, taken as a leitmotiv by the author, between the short story and novel close to the anti-epic, prevails in the hybrid fictional text of the parable. The myth provides the first step to this reading of time and differentiation between the sacred and profane space. Rereading from which paradigms have emerged of a critical work with the non-time in non-dissociation with space, conjunction built by an ironic look between fiction and history, (dys) topias about the fictional truth of Parábola do Cágado Velho. The three references derived from this reading receive the following titles in this thesis: the novelistic structure of Parábola do Cágado Velho; place and non-place in defining the narrative- imaginary structure; Pepetela and the mythical symbols in translation (dystopian). In its three faces, utopianism is revealed as a way of thinking founding possibilities of transformations which multiply utopias: structural difference of this Angolan novel